Participação política nas decisões estratégicas de preservação da biodiversidade : análise do Conselho Nacional do Meio Ambiente - Paes, Luciano Marcos (My University, 2017)
The research theme of the present work is a political participation in the strategic decisions of preservation of biodiversity – analysis of the National Council of the Environment. This study has as the theoretical object the active political participation as an operative aspect of social control in the delimitation of public policies for the conservation of biodiversity. For better systematization, three guiding premises were established: 1) The social control over State actions is only possible with active political participation; 2) The effectiveness of social control over State actions find obstacles to its operationalization; 3) The social control over the state in the environmental issue, at the national level, can be identified through the deliberations made by CONAMA, through the called administrative acts, which legally entitle, active participation of different collective subjects, representatives of the State and civil society. Using the dialectic method, we opted for a quantitative-qualitative or mixed approach, employing the analysis of content through a particular combination of bibliographical and documentary research. The results obtained made it possible to infer that the simple creation of Rights and Public Policy Councils don’t guarantee active participation once they don’t have the power to eliminate the inheritance, the problems and the challenges recorded in the Brazilian political culture. In the same way, they also represent another obstacle to the structural reforms of the State implemented since the 1990s, because, even with the definitions established in the legislation, these aren’t sufficient to reduce the considerable distance between the legal country and the real country. The conclusions achieved aren’t definitive, but allow to affirm, from the theoretical base that guided this work, that the active political participation is really essential, that is, it happens or there isn’t any chance of the social control established in the legal apparatus actually occur. With the study accomplished it hasn’t yet been possible to indicate the path to be followed in order to consolidate the desired social control of the State, once there is a need for further investigation, however, it’s believed that politic is always a way of sharing destinations, not just dominating or direct, and, it requires full use of the democratic resource to dialogue, negotiation, articulation among all involved, that is, it requires active political participation.
O tema de pesquisa do presente trabalho é a participação política nas decisões estratégicas de preservação da biodiversidade – análise do Conselho Nacional do Meio Ambiente. Tal estudo tem como objeto teórico a participação política ativa enquanto aspecto operacionalizador do controle social na delimitação das políticas públicas de conservação da biodiversidade. Para melhor sistematização foram estabelecidas três premissas orientadoras: 1) O controle social sobre as ações do Estado somente é possível com participação política ativa; 2) A efetivação do controle social sobre as ações do Estado encontram entraves na sua operacionalização; 3) O controle social sobre o Estado na questão ambiental, em nível nacional, pode ser identificado via as deliberações efetuadas pelo CONAMA, através dos denominados atos administrativos, que ensejam legalmente, participação ativa de diferentes sujeitos coletivos, representantes do Estado e da sociedade civil. Utilizando-se o método dialético, optou-se por uma abordagem quanti-qualitativa ou mista, empregando a análise de conteúdo via combinação particular entre pesquisas, bibliográfica e documental. Os resultados obtidos tornaram possível inferir que a simples criação de Conselhos de Direitos e Políticas Públicas não garantem a participação ativa uma vez que não possuem o condão de eliminar a herança, os problemas e os desafios gravados na cultura política brasileira. Igualmente, representam outro entrave as reformas estruturais do Estado implementadas a partir dos anos 1990, pois, mesmo com as definições estabelecidas na legislação, essas não são suficientes para reduzir a considerável distância entre o país legal e o país real. As conclusões alcançadas não são definitivas, mas permitem afirmar, a partir da base teórica que norteou este trabalho, que a participação política ativa é realmente imprescindível, ou seja, ela acontece ou não há chance alguma do controle social estabelecido no aparato legal ocorrer de fato. Com o estudo realizado ainda não foi possível indicar qual o caminho a ser trilhado para a consolidação do almejado controle social do Estado uma vez que há a necessidade de maiores aprofundamentos, entretanto, acredita-se que a política é sempre uma forma de compartilhar destinos, não apenas de dominar ou dirigir, e, requer o pleno emprego do recurso democrático ao diálogo, à negociação, à articulação, entre todos os envolvidos, isto é, exige participação política ativa.
Keywords: Participação política; Desenvolvimento sustentável; Biodiversidade - Preservação; Política pública; Direito ambiental; Political participation; Sustainable development; Biodiversity - Preservation; Public policy; Environmental law